Epidemiological study of COVID-19 in Mizoram, India: Meta-analysis of sociodemographic determinants, risk factors, and outcome - Gracy Laldinmawii; Pachuau Lalmalsawma; Rebecca Lalngaihzuali; Swagnik Roy; Zomuanpuii Colney; Gabriel Lalchandama; Praseena K; Jacinta Lalhmunsangi; Vanlalhmingthanpuii; Lalrinpari Sailo; et al. (Asian Journal of Medical Sciences, 2023)
Background: The impact of COVID-19 pandemic has shifted the livelihood of the global community including Mizoram which is located in the north-east region of India. Universal preventive measures have been implemented to reduce the spread of the virus. Aims and Objectives: The aim of this study is the epidemiological and clinical characterization of patients infected with SARS-COV-2. The aim of the study was to examine the sociodemographic determinants and risk factors of the disease severity with COVID-19 patients. Materials and Methods: A multicenter and cross-sectional study on patients who have been diagnosed and confirmed of SARS CoV2 infection of the Mizo Community. The data were collected by professionals from April 2020 to May 2022. Sociodemographic determinants, clinical presentation, comorbidities, livelihood, alcohol, and tobacco consumptions were described. All data were analyze using SPSS 22 version. The association of the variables with ct value (≤25 and >25) of COVID-19 was examined using Chi-square and logistic regression model and P<0.05 as statistically significant. Results: A total number of 19,25,885 samples were tested among which 2,27,849 cases were diagnosed with COVID-19 from March 24, 2020, to May 12, 2022, in Mizoram. The mean±SD age of the analytic population was 30.10±19.64 years. Female was more infected and patients between the age of 16–30 years represent the most frequent age group in the population study. About 55.2% were symptomatic patients with mortality rate at 0.30% as of May 12, 2022. Conclusion: In this cross-sectional study, a wide range of sociodemographic risk factors, including socioeconomic status, racial/ethnic minority status, household composition, and environmental factors, was significantly associated with COVID-19 incidence and mortality. To address inequities in the burden of the COVID-19 pandemic, these social vulnerabilities and their root causes must be addressed.